The Importance of Rehabilitation Programs Using Balneary Treatments in Patients with Spinal Cord Injury - Doinita Oprea; Madalina Gabriela Iliescu; Elena Valentina Ionescu; Liliana Elena Stanciu; Lucian Petcu; Sorin Chiriac; Andra Maria Stefan; Diana Victoria Gidu; Antoanela Oltean; Viorela Mihaela Ciortea; Carmen Oprea (Applied Sciences, 2022)
The rehabilitation tools that are designed to improve the function of patients with spinal cord injury (SCI) have various effects. The goals of rehabilitation are to prevent secondary complications, maximize physical functioning, and integrate them into the community. The objective of this study is to evaluate the functional and neurological outcomes of patients with SCI after in-patient rehabilitation in a balneary unit. Methods: one hundred forty-two patients, admitted for primary rehabilitation in a two-year period (2020–2021), aged ≥18 years with SCI, divided into traumatic SCI (T-SCI) and nontraumatic SCI (NT-SCI). The following demographic information was collected: gender, age, studies, occupation, and environment. All patients underwent an initial clinical examination which included diagnosis, causes of SCI, medication, Carmeli score, fall risk, Visual Analogue Scale (VAS) for pain, Functional Independence Measure Motor (FIMm), Functional Independence Measure Cognitive (FIMc), and Functional Independence Measure Total (FIMt). At discharge, the fall risk, VAS, FIMm, FIMc, and FIMt were analyzed. We compared the results between the two groups. Results: T-SCI group was 65 (45.77%) and the NT-SCI group was 77 (54.23%). The study analyzed the effects of rehabilitation on the functional presentation of patients with SCI. It also compared the effects of rehabilitation on T-SCI versus NT-SCI on different outcomes such as age, gender, and clinical–functional impairment. Conclusions: Physical medicine and rehabilitation increase the autonomy of patients. Neurological improvement begins in the first 10 days of complex rehabilitation treatment and is not significantly different between the two groups. The cause of the injury in SCI does not affect the results of the rehabilitation.